DAMPAK LIBERALISASI PERDAGANGAN GLOBAL DAN PERUBAHAN KONDISI EKONOMI-POLITIK DOMESTIK TERHADAP DINAMIKA PERDAGANGAN LUAR NEGERI KELOMPOK KOMODITAS BERBASIS PERTANIAN DI INDONESIA - RAHMANTO, BAMBANG (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006)
Impact of global trade liberalism and domestically of economic and political change to the dynamism of foreign trade of Indonesian agriculture product. The implementation of global trade liberalism as a result of the agreement of agriculture WTO-1994 is accused to provide more benefit to developed countries than developing countries. Phenomena of economic crisis and implementation of autonomy process is also assumed to be strongly influence to create the dynamism of foreign trade of Indonesian agriculture product. This study is conducted to identify the impact of those phenomena. The outcome of the study identifies that aggregately the role of agriculture commodity group is decreased in both the contribution surplus of Indonesian foreign trade and its growth during global trade liberalism period. Meanwhile, the result of desegregation analysis by regression method indicate that global trade liberalism has significance effect in increasingly deficit trade of commodity group of cereal, sugar, milk, live animal, and residues product of milling industry. Otherwise, affect significantly in increasing surplus to commodity group that related to fishery, estate and preparation products. Condition of crisis economic tend to decrease of deficit of some commodity group that was ever deficit, except for commodity group of sugar. For surpluses commodity group, the effect are varied. During implementation of autonomy process indicate that deficit of commodity group of sugar and cereal was decreases as a result of government intervention in controlling import surge of sugar and rice.
Keywords: oTrade liberalism, Economic Crisis, Autonomy, Agricultural Commodities.